การปรับปรุงสมบัติต้านจุลินทรีย์ของผ้าฝ้ายด้วยน้ำมันหอมระเหยข่าและสารสกัดข่า - จิตต์โสภา เฉลียวศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The utilization of Thai herbs (galangal) on improvement of the antimicrobial property on cotton fabric was investigated. Two different types of galangal (commercial galangal essential oil and prepared galangal extracts) were treated onto cotton fabric by using pad-dry technique. The antimicrobial activity against Staphylococcus aureus according to AATCC Test Method 100-1999 was then evaluated. The galangal extracts were prepared by extracting dried rhizomes and fresh rhizomes with ethanol at 2 different conditions 1) room temperature for 1 day 2) 60oC for 45 min. The prepared galangal extracts was then finished on cotton fabric at various concentrations of 0.5 and 1%. It was found that percentage of reduction of bacteria of the unfinished cotton fabric was only 56.3%, whereas, the percentage of reduction of bacteria of the finished cotton fabrics with galangal extracts from dried rhizome at the concentration of 0.5 and 1% were 72.9 and 99.9%, respectively. In case of galangal extracts from fresh rhizome, the percentage of reduction of bacteria of the finished was only 95.6%. Thus, when the composition of the antibacterial agent determined by GC-MS technique, the high percentage of reduction of bacteria (99.9%) and the energy consumption were considered, the extraction of galangal from dried rhizomes by soaking with ethanol at room temperature for 1 day and the concentration of 1% finished on cotton fabric was appropriate. Similarly, when cotton fabrics were finished with commercial galangal essential oil at various concentrations of 1, 3, 5 and 10%, the percentage of reduction of bacteria were 85.4, 91.9, 91.8 และ 99.3, respectively. Since the usage of essential oil has a restriction not over 5% due to a skin irritation to the user, the optimal concentration of essential oil for applying onto cotton fabric in this study is 3% concentration. In addition, durability of antimicrobial performance of the finished cotton fabric with essential oil and galangal extracts from dried rhizome to washing, to light, to perspiration, to hot press and color change of cotton fabric after finishing were also examined. It was found that both types of antimicrobial agents were durable to washing but non-durable to perspiration. Galangal extracts from dried rhizome was more durable to light and hot press than essential oil but caused the color of finished fabric more yellow than essential oil.